Digital portfolios application: a tool to become a reflective ESL teacher - Low, Xiang Yein; Mok, Angeline En Ket; Othman, Moomala; Ismail, Lilliati; Aralas, Dalia (Human Resource Management Academic Research Society, 2017)
The use of portfolios has been promoted in professional development among teachers especially in conducting reflective teaching. However, many teachers found developing portfolios to be time, energy and space consuming with the number of workloads and amount of documentations in school. When doing reflective teaching, teachers also tend to concentrate on their teaching practices and overlook their students’ learning and progress. These issues can be overcome with the use of digital portfolio applications. Digital portfolio applications enable teachers to collaborate with students in creating digital portfolios for different classrooms on iPads, smartphones and laptops. Teachers can create documents like journals or upload materials to be shared with students through the application. Students can add artifacts of different forms to the digital portfolios. With digital portfolio applications, teachers can check students’ assignments and give comments as well. Students can also provide the teachers with feedbacks by writing what they have learned and their comments for lessons. Thus, teachers can create a more comprehensive and systematic portfolio with unlimited storage amount to conduct teaching and learning, document progress and carry out reflective teaching effectively. Such applications also bring convenience as it can be accessed easily with the use of electronic gadgets or devices.